Maternal characteristics and delivery method in patients with preeclampsia in PKU Muhammadiyah Bantul, Yogyakarta - Irfan Rahmatullah; Rachma Greta Perdana Putri; Tiara Ismirahmadani; Novi Sukirto (Ahmad Dahlan Medical Journal, 2023)
Preeclampsia is the condition of pregnancy that has high mortality of mother and result some complication for the childbirth. The incidence of preeclampsia in the world reaches 10% whereas 3% -5% of them experience complications of eclamptic pregnancy. The objective of this study was to explore maternal characteristics and delivery methods of preeclampsia in order to predict the prognosis of the diseases and direct proper antenatal care. Methods: the study was Descriptive observational with a cross-sectional design at PKU Muhammadiyah Bantul during 2018-2020. Data were collected from medical records. The variables was compared using the Mann-whitney, kruskall wallis, and crosstabs as appropriate. Results: In this study, we found 77 women. Majority of patient’s age are less than 35 years old, 5 patients (6.50%) were mild preeclampsia and 52 patients (67.50%) were severe preeclampsia. Forty seven (61.04%) patients with preeclampsia were multigravida and 37 patients (48.05%) have normal BMI. Almost all patients without comorbid disease (96.10%) and history of preeclampsia (98.70%). Sixty eight patients (88.31%) have interpregnancy interval less than 5 years and without complication after delivery. Preeclampsia’s patients delivered at aterm gestational age (67.53%). Significantly, delivery method of the patients were cesarean section (74.03%; p = 0.01%).